PERSEPSI MAHASISWA PENDIDIKAN TEKNIK MESIN PADA PELAKSANAAN PROGRAM PENGALAMAN LAPANGAN SATUAN PENDIDIKAN DIMASA PANDEMI COVID-19 - Mu’min, Mu’min; Sukrawan, Yusep; Wiyono, Apri (Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to determine the Perceptions of Educational Students, Engineering, Machines in the Implementation of the Education Unit Field Experience Program (PPLSP) in terms of pedagogical competence and social competence during the Covid-19 pandemic. This research was conducted at the University of Education of Indonesia (UPI) with the research subject, namely students participating in the 2020 PPLSP Mechanical Engineering Education batch of 2016. The research was conducted in August 2020. With a total population of 48 respondents. The sampling technique used a questionnaire / questionnaire. The data analysis technique used descriptive analysis.The results of this study indicate that:The mastery of pedagogical competence (learning planning, learning implementation, and assessment) with a mean value of 87.96 means that they are in the 81-99 interval class (Good) by obtaining a total of 29 students as respondents. or 60.4%. In the implementation of PPLSP, the pedagogical competence which includes learning planning, learning implementation and assessment is in the